Sellar hemangiopericytoma masquerading as pituitary adenoma: an overlooked intriguing case study unveiling a rare surgical conundrum - Ebrahimzadeh, Kaveh; Mirahmadi Eraghi, Mohammad; Ansari, Mohammad; Dmytriw, Adam A. (Frontiers in Surgery, 2024)
Hemangiopericytoma (HPC) constitutes less than 1% of all primary central nervous system tumors. It is a vascular neoplasm with potential malignancy that, in rare instances, manifests as a primary lesion within the brain. Typically, it originates from the meninges. Here, we describe an exceptionally uncommon sellar region solitary fibrous tumor/hemangiopericytoma (SFT/HPC) that mimicked a nonfunctional pituitary adenoma. Introduction and Importance: Case Presentation: A 54-year-old male was referred to our hospital due to progressive blurred vision in the left eye over the past year. A homogeneous iso-dense extra-axial intrasellar round mass with extension into the suprasellar region, mainly on the left side, along with bony erosion and osteolysis around the sellar region, was observed on a brain CT scan. Brain MRI revealed a well-defined 251713 mm mass with iso-signal on T1-weighted images and hypersignal on T2-weighted images, originating from the pituitary gland within the sella turcica. The mass avidly enhanced following Gadolinium injection and adhered to both carotid arteries without vascular compression or invasion. It extended to the suprasellar cistern and compressed the optic chiasm. The diagnosis was nonfunctional pituitary macroadenoma, leading to the decision for Endoscopic Trans-Sphenoidal Surgery (ETSS). A non-sustainable, soft, grayish mass was grossly and totally resected during the operation. Subsequently, there was a significant improvement in visual acuity during the early postoperative period. Histopathologic examination confirmed hemangiopericytoma (WHO grade II). Conclusion: Due to its malignant nature, hemangiopericytoma should be included in the differential diagnosis of a sellar mass, both from a clinical and morphological perspective.